Effect of Two Different Doses of Vitamin D Supplementation on Metabolic Profiles of Insulin-Resistant Patients with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial - Foroozanfard, Fatemeh; Talebi, Maesoomeh; Samimi, Mansooreh; Mehrabi, Sahar; Badehnoosh, Bita; Jamilian, Mehri; Maktabi, Maryam; Asemi, Zatollah (Hormone and Metabolic Research, 2017)
The current study was conducted to evaluate the effects of 2 different doses of vitamin D supplementation on metabolic profiles of insulin-resistant patients with polycystic ovary syndrome (PCOS). This randomized double-blind, placebo-controlled trial was performed on 90 insulin-resistant patients with PCOS according to the Rotterdam criteria aged 18–40 years old. Participants were randomly allocated into 3 groups to receive either 4 000 IU of vitamin D (n=30) or 1 000 IU of vitamin D (n=30) or placebo (n=30) per day for 12 weeks. Vitamin D supplementation (4 000 IU), compared with vitamin D (1 000 IU) and placebo, led to reduced fasting plasma glucose (−4.3±8.6 vs. −4.7±7.1 and +0.1±6.7 mg/dl, respectively, p=0.02), serum insulin concentrations (−2.7±2.7 vs. −1.4±4.2 and −0.1±4.1 μIU/ml, respectively, p=0.02), and HOMA-IR (−0.6±0.6 vs. −0.4±1.0 and −0.1±0.9, respectively, p=0.02). In addition, we found significant decreases in mean change of serum triglycerides (−10.3±7.3 vs. −3.6±14.5 and +6.9±23.8 mg/dl, respectively, p=0.001), VLDL- (−2.0±1.5 vs. −0.7±2.9 and +1.4±4.8 mg/dl, respectively, p=0.001), total- (−14.0±9.5 vs. −6.2±24.0 and +7.1±29.7 mg/dl, respectively, p=0.002), LDL- (−10.8±8.3 vs. −5.7±21.9 and +6.8±28.2 mg/dl, respectively, p=0.005), and total-/HDL-cholesterol ratio (−0.2±0.3 vs. −0.1±0.6 and +0.2±0.7 mg/dl, respectively, p=0.003) in the high-dose vitamin D group compared with low-dose vitamin D and placebo groups. Overall, vitamin D supplementation at a dosage of 4 000 IU/day for 12 weeks in insulin-resistant patients with PCOS had beneficial effects of glucose metabolism and lipid profiles compared with 1 000 IU/day of vitamin D and placebo groups.